Penguatan Peran Masyarakat Bidara Cina dalam Adaptasi dan Mitigasi Bencana Banjir - Narulita, Sari; Nur Aulia, Rihlah; Handawati, Rayuna; Kusumawati, Lia; Khoiru Salsabilla, Qibtiyah (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The background for this activity is the low level of climate literacy and climate literacy in the community. Many people still think that flooding is a destiny that makes them surrender to the conditions that occur, so they are not ready to anticipate and minimize their impact. The activity with the theme of Strengthening Community Roles in Mitigation and Adaptation to Flood Disasters was attended by representatives of RT/RW in the Bidara Cina sub-district. The activity is carried out with a concept that involves the active participation of participants until the expected reinforcement occurs. The material includes Climate Literacy, Government Policy for climate change mitigation, flood mitigation and the validation of evacuation routes. The community's response is entirely reasonable to the activities carried out, and hopes that similar activities can continue to be carried out to increase public understanding of climate literacy and disaster literacy.